Penyederhanaan dan Penyempurnaan Sistem Pemilu di Indonesia - ikhsan fatah yasin (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2017)
The issue of multi-party presidential governance in Indonesia remains an unfinished homework to date, many political experts and Constitutional Law have inferred the ineffectiveness of presidential systems in multi-party models. On the other hand, our Constitution has affirmed through its characteristics that Indonesia embraces a presidential government system, but it is applied in multiparty political construction. Since the beginning of the general election, Indonesia still uses the proportional system with various color additions district. Because of the proportional success that has been used since the first election, it may be necessary to try new things by using the district system with a variety of variations so as not to undermine democracy. The parliamentary threshold model and the tightening of conditions for parties to follow the election will slowly simplify the party. Nevertheless, the high standard of parliamentary threshold creates much criticism, the small party feels aggrieved and says it is against democracy.